Formation of Barium Strontium Titanate Powder by Solid State Reaction using Different Calcination Temperatures - Wah Tzu, Teoh,; Fauzi Mohd Noor, Ahmad; Arifin Ahmad, Zainal (Malaysian Journal of Science, 2002)
The unique electrical properties of large permittivity in Barium Strontium Titanate have been widely used to make capacitors; it can be produced by solid state reaction. In this study, the mixture of Barium Carbonate, Strontium Carbonate and Titanium Dioxide was calcined at 500°C, 1000°C, 1100°C, 1150°C, 1200°C, 1250°C and 1300°C. The results of the phases change in each stage were investigated via X-Ray Diffraction. The results show that the formation of Barium Strontium Titanate started at 1100°C with the presence of other phases. The mixture is fully reacted to form Barium Strontium Titanate at 1150°C. Only Barium Strontium Titanate was formed as the calcination temperature was set higher.